Religious heritage in the North. Monocultural or multicultural? - Amundsen, Arne Bugge (Approaching Religion, 2023)
The article takes as its point of departure the notion that the Scandinavian countries have been dominated by a monocultural Lutheranism. This notion is nuanced by focusing on everyday life and oppositional voices. In the nineteenth century, the Lutheran state churches began to interpret their past as religious cultural heritage. Focusing especially on Norway, it is argued that this monocultural perspective has been replaced by a multicultural one with emphasis on ethnic minorities and indigenous religious heritage, dialogue and tolerance.
Keywords: Scandinavian Lutheranism; religious cultural heritage